Fluconazole Resistance in C. Tropicalis by Broth Microdilution Method and to compare the relative gene expression of erg11 gene in both Fluconazole Resistant and Sensitive C Tropiocalis - Sahar Imtiaz, Sidrah Saleem, Sonia Tahir, Muhammad Imran, Shah Jahan, Sila Imtiaz (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate fluconazole resistance among C. tropicalis by broth micro dilution methodand relative expression of ergosterol(ERG11) gene in fluconazole resistant and sensitive Candida tropicalis. Methods: The study design was comparative study conducted inMicrobiology Department of UHS.A sum up of 66 confirmed isolates of Candidatropicalis were attained from Jinnah Hospital, Lahore. The fluconazoleesistance of the isolates was determined by broth microdilution methodand the relative gene expression of ERG11 gene was analyzed by real time PCR, in Microbiology Department of UHS. Results: The antibiotic susceptibility testing of C.tropicalis showed fifty one fluconazole sensitive, eight susceptible dose dependent and seven fluconazole resistantC. tropicalis. Relative gene expression ofERG11gene showed anincrease expression about 2.0 fold in C. tropicalis resistant isolates than C. tropicalis susceptible isolates. Globally, C. albicanswas the most frequently isolated species but now there is a decline in trendwith increase figures for non-albicans Candida species. Thesenon-candidaalbicans are now emerging as resistant species and cause serious ailments. This study showed seven fluconazole resistant C. tropicalis among sixty six isolates by broth microdilution method. Further on molecular testing by relative gene expression of ERG11 gene it was noticed that these resistant isolates have 2.0 fold increased mRNA expression levels of this gene as compared to sensitive strains. Conclusion: C. tropicalis was found to be resistant to fluconazole. Ergosterol expression was markedly raised in fluconazole resistant C. tropicalis in contrasted to drug sensitive C. tropicalis. Keywords: C. tropicalis, fluconazole resistance antifungal susceptibility testing, non-albicans Candida, broth microdilution method, relative gene expression.